Harmonization of cyclical construction processes: a systematic review. (2017) - Zavadskas, Edmundas Kazimieras; Vilutienė, Tatjana; Tamošaitienė, Jolanta
Abstract: Sustainable development is first defined as development that satisfies the needs of the present without compromising the ability of future generations to satisfy theirs. Sustainable development is possible if conditions of respect for the environment, preventing the exhaustion of natural resources and preserving the overall balance, are fulfilled. The necessity of the development and maintenance of habitats also emphasized. Construction processes have important role in creation of built environment and their impacts have to be measured as construction contributes to air pollution, land use and contamination, usage of resources, water and materials depletion, water pollution, impacts on human health, and climate change. Previous (own) research revealed, that the key categories of Web of Science, which encompass the research on the sustainable built environment, cover construction and building technologies, environmental science and studies, and civil engineering. The article presents a review of the literature on efforts to harmonize the construction processes, which was made on the basis of the Web of Science Core Collection database. The analysis of the number of publications was made according to years of publication and research areas. To honour the contribution made by Prof Oleg Kapliński in the field of Sustainable Development and Decision-Making, and to commemorate his 75th anniversary, this article also highlights his academic career and research.